Una aproximación al acto cambiario desde la teoría del negocio jurídico - Da Giau Roose, Piero (Universidad ESAN, 2020)
The general principles of law are a worldview or aspiration that generate guidelines that go beyond the creative work of positive law, covering not only the act generator of the legal norm but also the mechanisms of interpretation and legal integration. However, each area of law is ruled by special principles that are its own and that generate individual characteristics that make them independent. This article seeks to relate the rules that govern the legal transactions with those that deal with the exchange law, trying to demonstrate the singularities inherent in this special area of law, we will start from a historical perspective and culminate in the normative and jurisprudential demonstration, reinforced by dogmatic in both fields of legal knowledge.

Los principios generales del derecho constituyen una cosmovisión o aspiración generadora de pautas orientadoras o directrices que van más allá de la labor creadora del derecho positivo; abarcan no solo el acto generador de la norma jurídica, sino también los mecanismos de interpretación y de integración jurídica. Empero, cada área del derecho se rige por principios especiales que les son propios y que generan características individuales que las independizan. El presente artículo busca relacionar las normas que rigen al negocio jurídico con aquellas que tratan sobre el derecho cartular o cambiario, intentando demostrar las peculiaridades inherentes a esta última y especialísima área del derecho. Partiremos desde una perspectiva histórica y culminaremos en la demostración normativa y jurisprudencial, reforzada por la dogmática en ambos campos del conocimiento jurídico.
Keywords: General principles of law; Exchange principles; Integration; Interpretation; Legal transactions; Principios generales de derecho; Principios cambiarios; Exchange law; Integración; Interpretación; Securities; Negocio jurídico; Error; Derecho cambiario; Título valor; Form; Error; Formality; Forma; Formalidad; Capacity; Capacidad; Manifestación de voluntad; Manifestation of will, literality; Literalidad; Documentation; Documentación; Especialidad; Specialty; Antinomias; https://purl.org/pe-repo/ocde/ford#5.05.01